Investigation Of The Relationship of Eating Attitudes With Thought Shape Fusion, Gender and Body Mass Index - Sultan OKUMUSOGLU (Muhammed Yıldız, 2017)
Certain patologies are accepted as characterized with relevant certain cognitive distortions. Eating Disorders and Obssessive Compulsive Disorders (OCD) are related in terms of comorbidite, existence of similar distortions and intrusive thoughts. Distorted cognitions related with body shape and weight are associated with eating disorders and the distorted cognition which was conceptualised as thought shape fusion is accepted as a version of thought action fusion which is commonly seen at OCD. Because of its practical and theoretical relevance the aim of the present study is investigation of the relationship of eating attitudes of individuals with thought shape fusion cognitive distortion and gender and body mass index (BMI). Participants are 73 university students with age range 18-28 (58 male). Eating Attitudes Test (EAT) and Thought Shape Fusion Scale (TSFS) have been used for data collection. A positive correlation was found between TSFS and EAT (r= 0.53, p=0.01) and TSFS and BMI (r=0,34, p=0,01). According to stepwise regression analysis primary predictor of TSFS scores are EAT scores; %28 of the variance of the TSFS was explained by EAT scores and when BMI and gender variables are added the explained variance is %47. Women differed with significantly higher means in terms of EAT scores. Groups were formed according to pathology cut point of EAT scale (≥30) and the group above the cut point differed with significantly higher TSFS mean scores. Results of the present study seems parallel with the claims which associates eating disorders with distorted cognitions which are expressions of intrusive thoughts similar to OCD and associated with characteristics of eating disorders as overrating of food, body weight and shape. Findings are evaluated as having practical and theoretical significance. It is hoped that after supported with future studies the findings of the present study will be useful by adding to the existing knowledge in the field which associated with the efforts about determination of certain cognitive distortions to increase therapeutic outcome